2020
DOI: 10.1155/2020/2946541
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchiasis in Patients with Biliary and Pancreatic Diseases: Diagnosis and Risk Factors

Abstract: Background. Many epidemiological studies have investigated the risk factors for clonorchiasis, but endoscopic findings of this disease in endoscopic retrograde cholangiopancreatography (ERCP) have not been well characterized. In this study, we evaluated clonorchiasis in ERCP in patients with biliary and pancreatic diseases. Methods. This was a retrospective two-center study in hospitalized patients who received ERCP between January 2012 and October 2018. All patients were divided into clonorchiasis and nonclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…DNA detection for C. sinensis aids in confirmation but is impractical for screening due to cost and time constraints [ 3 ]. Liao, G et al reported that C. sinensis eggs were significantly higher in bile than in fecal samples, indicating bile as a preferable specimen in case of biliary obstruction [ 9 ]. Currently, diagnosis often hinges on routine examinations like diffuse IHBD dilation, peri-bile duct echo, and gallbladder floating objects, alongside a significant eosinophil elevation in routine blood examination [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA detection for C. sinensis aids in confirmation but is impractical for screening due to cost and time constraints [ 3 ]. Liao, G et al reported that C. sinensis eggs were significantly higher in bile than in fecal samples, indicating bile as a preferable specimen in case of biliary obstruction [ 9 ]. Currently, diagnosis often hinges on routine examinations like diffuse IHBD dilation, peri-bile duct echo, and gallbladder floating objects, alongside a significant eosinophil elevation in routine blood examination [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%